2009
DOI: 10.1175/2009waf2222269.1
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of Spatial Forecast Verification Methods

Abstract: Advancements in weather forecast models and their enhanced resolution have led to substantially improved and more realistic-appearing forecasts for some variables. However, traditional verification scores often indicate poor performance because of the increased small-scale variability so that the true quality of the forecasts is not always characterized well. As a result, numerous new methods for verifying these forecasts have been proposed. These new methods can mostly be classified into two overall categorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
301
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(307 citation statements)
references
References 47 publications
0
301
0
6
Order By: Relevance
“…The issues with verifying km-scale precipitation forecasts are well established in the literature, with many developed spatial verification methods rewarding close forecasts (e.g. Gilleland et al, 2009, provide a review), and it is hypothesised that the results shown here are similar to what is seen for high-resolution precipitation forecasts verified against gauges. A preliminary test of this hypothesis is offered here, using the 'minimum coverage' spatial method proposed by Damrath (2004) which enables a point observation to be compared to a forecast neighbourhood (instead of just the nearest grid point).…”
Section: Total Cloud Amountmentioning
confidence: 62%
“…The issues with verifying km-scale precipitation forecasts are well established in the literature, with many developed spatial verification methods rewarding close forecasts (e.g. Gilleland et al, 2009, provide a review), and it is hypothesised that the results shown here are similar to what is seen for high-resolution precipitation forecasts verified against gauges. A preliminary test of this hypothesis is offered here, using the 'minimum coverage' spatial method proposed by Damrath (2004) which enables a point observation to be compared to a forecast neighbourhood (instead of just the nearest grid point).…”
Section: Total Cloud Amountmentioning
confidence: 62%
“…In order to allow for an evaluation of the small-scale structure of precipitation, new verification techniques have been developed in recent years. According to Gilleland et al (2009), the different methods can be grouped into four categories: (i) neighbourhood (or fuzzy), (ii) scale separation (or scale decomposition), (iii) feature-based (or objectbased), and (iv) field deformation.…”
Section: Introductionmentioning
confidence: 99%
“…This concept has also been used for forecast verification purposes, e.g. (Ebert, 2008), (Gilleland et al, 2009) and (Ebert, 2009). …”
Section: Neighbourhood Inclusion Methodsmentioning
confidence: 99%
“…If the magnitude of a weather event is correctly forecasted but slightly displaced in space then the model will be penalized twice: once for missing the observations and once again for giving a false alarm; this is known as the ''double penalty'' (Michaelides, 2008). Hence the value of using a finer spatial resolution may be underestimated when using traditional verification procedures, and two overall categories of new performance evaluation methods have therefore been developed: filtering methods and displacement methods (Gilleland et al, 2009). …”
Section: Introductionmentioning
confidence: 99%